Abstracts of oral and poster presentations given at the 8th International Workshop on Grapevine Trunk Diseases, Valencia, Spain, 18–21 June 2012 - VV., AA. (Phytopathologia Mediterranea, 2012)
The 8th International Workshop on Grapevine Trunk Diseases was held in Valencia, Spain, on June 18–21 2012. The meeting was attended by 120 participants and 103 papers were presented either as oral or poster presentations in four sessions: Pathogen Detection and Characterization, Epidemiology, Host-Pathogen Interaction and Disease Management. A special session was dedicated on implications of trunk diseases for grapevine nurseries with five invited presentations, followed by several oral and poster presentations. A field trip to the Utiel-Requena wine-producing area was undertaken on June the 20th, including visits to vineyards and a winery. The workshop is the 8th organised by members of the International Council on Grapevine Trunk Diseases (www.icgtd.org), a subject matter committee of the International Society for Plant Pathology (www.isppweb.org).